Plant polyphenolic extracts as potential human anti-hepatocarcinoma agents - Martinez, Maria Julia (2014)
Plant polyphenols are secondary metabolites, primarily synthesized to protect plants from biotic and abiotic stresses. These compounds are found in fruits, vegetables and beverages and are an important part of the human diet. Plant derived polyphenols have been described as antioxidant, antimicrobial and anticarcinogenic agents. Human hepatocellular carcinoma is one of the most common types of cancer worldwide and it is associated to high mortality. The development of new treatments for hepatocarcinoma is needed, and plant polyphenols appear as a promising important source of compounds for prevention and treatment of this disease. The aim of this article is to review the current knowledge about the use of plant polyphenolic extracts as potential agents for the treatment of human hepatocellular carcinoma.